An old woman with diffuse abdominal pain and abnormal imaging findings - Modesto dos Santos, Vitorino; França, Victor Eduardo Almeida; Dutra, Marcus Vinicius Ferreira (Revista de Medicina e Saúde de Brasília, 2017)
A 71-year-old woman had fever, intense abdominal pain and constipation intercalated with diarrhea during five days. Her antecedents were chronic obstructive pulmonary disease due to smoking. She denied alcoholism and use of illicit drugs. On admission she was febrile and eutrophic; with dyspnea, tachycardia and arterial hypotension. The abdomen was flaccid, with normal peristalsis, diffusely painful on superficial palpation and positive Murphy's sign, and absence of organomegaly. Laboratory tests showed anemia, leukocytosis, and elevation of liver enzymes. Worthy of note, were the computerized abdominal images, and finding of colonoscopy evaluation